Quercetin: Synergistic Interaction with Antibiotics against Colistin-Resistant Acinetobacter baumannii - Elif Odabaş Köse; Özlem Koyuncu Özyurt; Süreyya Bilmen; Hakan Er; Cansu Kilit; Esra Aydemir (MDPI AG, 2023)
Infections caused by resistant strains of Acinetobacter baumannii are now a global problem that requires the immediate development of new antimicrobial drugs. Combination therapy is one of the strategies used to solve this problem. Based on this information, the purpose of this study was to determine whether quercetin (QUE), in combination with three antibiotics, is effective against colistin-resistant A. baumannii strains (ColR-Ab). The effects of the combination of QUE with colistin (COL), amikacin (AMK), and meropenem (MEM) were evaluated according to the checkerboard synergy test. The combinations of QUE + COL and QUE + AMK showed synergistic activity on ColR-Ab strains with FICI values in the range of 0.1875-0.5 and 0.1875-0.2825, respectively. A 4- to 16-fold decrease in COL MIC and a 16- to 64-fold decrease in AMK MIC values were detected. Synergistic activity was confirmed by the time-kill test, and these combinations were found to be bactericidal at the end of 24 h. According to spectrophotometric measurements, the combinations of QUE + COL and QUE + AMK induced membrane damage, leading to the leakage of nucleic acids. Cell lysis and cell death were confirmed with SEM observations. The detected synergy offers an opportunity for the future development of treatment strategies for potential infections caused by ColR-Ab strains.